Alfredo Buzaid e a contrarrevolução burguesa de 1964: crítica histórico-imanente da ideologia do direito, da política e do Estado de Justiça - Machado, Rodolfo Costa (2015)
This dissertation searches to understand the indissoluble connection between the historic activity of Alfredo Buzaid (1914-1991) and his specific bourgeois-autocratic ideology, understanding the formative period of Buzaid s thought outlined by Plínio Salgado s Brazilian Integralism and explaining the role of Buzaid (beside the Law School of University of São Paulo) in the conspiracy of Ipês complex (Institute for Research and Social Studies). His emphatic Christian anti-communism is closely examined beneath juridical basis, and the CCC (Command of Communist Hunting) agents, but mainly under the social function accomplished by Buzaid while Minister of Justice of the dictator Emílio Médici (1969-1974). Pursuing the so called ―internal enemies‖ of the self-named Brazilian Democratic Revolution of 1964, the State s autocratic ideologist managed the official denial about the crimes against humanity perpetrated by the last Brazilian Bonapartist dictatorship. In this context, Buzaid coordinated the production of the ‗Book of Truth (1970), although it has never been published. After the Ministry of Justice, during The Cold War international disputies, Alfredo Buzaid engaged his anti-communist militancy on the ―Brazilian Chapter‖ of the World Anti-Communist League (WACL), presided by the official brazilian banker of Condor Operation. With the statutory ontology of Karl Marx, this dissertation is based on the achievements of José Chasin about the Military Dictatorship of 1964-1985 as a particular way of Brazilian s bonapartism (this means the bourgeoisie s indirect dominance). We also apprehend the bonapartist Buzaid s world view in the larger context of ‗1964 Ideology , in fact, ‗the rulers of the ‗atrophic capital that, under Médici, established as tenets the ‗accelerated development based upon on official terrorism , according to Antonio Rago Filho. In accord with the historic-immanent critic, the Law s ideology of Buzaid and his conception of law ―science‖ were systematized as processual technique able to carry out the rational Administration of the State s Justice. The rationalization and technicalization of the Judiciary and the process, as well as the mutual implications between Democracy and Process, were outlined by Buzaid to build the Judiciary s autocracy into rationalizing standard for the political representation supported by the others suffraged State Powers, intending to ―save‖ de democracy from the common people. Therefore, the autocratic-technician reason as criterion for the highest state charges to repress the ―auspicious phenomenom of common people s rising‖. It is possible to grasp Buzaid s engagement at a social democracy type based on the Catholic Church s doctrine, the turning point when he contradictorily ―demonizes‖ the bourgeois technician and rationality that has made the world unsacred. Finally, we have examined the bonapartist ideology of Buzaid that supported the permanent bourgeois counter-revolution of 1964-1985. After the development of a spiritualist conception of human being, of history, State, Government, Law and its positive laws, Alfredo Buzaid has defended the establishment of a brazilian―real democracy‖, anti-communist and anti-liberal State of Justice, setting his ultra-reactionary class position at the conflict Christianity versus Marxism and atheism. Buzaid turns Camões into a medieval character and becomes an apologist of the Empire s demiurges of 1822, appearing as an anachronistic chronicler of State s greatest man. Buzaid has also ascribed the spiritualist conception of human being to the political philosophy of the 1964 counter-revolution s State of Justice, assigning with Christian ethic and morality institutionalized against the atheist communism. At last, the bourgeois counter-revolutionary constitutional law in Brazil is taken as particularity of bonapartist ideology and its accelerated economic development combined with maximum national security. Rationalization and technicalization appear, to Alfredo Buzaid, as technical-autocratic reason hostile and averse to political control exerted by the universal and direct suffrage, the bourgeois political domination kind wich is typical of classic European capitalist modernity. His processual judiciary reason represents one step behind concerning to the bourgeois classic parliamentary politic reason, expressing Buzaid s world view, in the historic praxis, the bourgeois-autocratic vocation of jurists and legal technicians able to regressively ―spiritualize‖ dictatorships and State s terrorisms, serving the great capital